Antifungal activity of Mentha piperita and Carum carvi essential oils - Plavšić Dragana V.; Dimić Gordana R.; Psodorov Đorđe B.; Psodorov Dragan Đ.; Šarić Ljubiša Ć.; Čabarkapa Ivana S.; Košutić Milenko B. (Zbornik Matice Srpske za Prirodne Nauke, 2017)
Aromatic plants are one of the most important sources of biologically active secondary metabolites, which possess various antimicrobial characteristics. The aim of this work was to examine the effect of antifungal activities of mint and caraway essential oils against the selected fungi. Eight species of molds were selected for antifungal testing: Alternaria alternata, Aspegillus flavus, A. niger, A. versicolor, Eurotium herbariorum, Penicillium aurantiogriseum, P. chrysogenum and P. expansum. Testing of essential oils antifungal activity against the selected species was conducted using the disc diffusion method by adding mint and caraway essential oils (0.5, 1, 5, and 10 μl per disc). Antifungal activity of essential oils was expressed by the diameter of inhibition zone (mm). The most powerful effect of mint essential oil was recorded against E. herbariorum, as its growth was completely inhibited by the quantity of 5 μl. The weakest inhibitory effect was observed against P. chrysogenum (inhibition zone 13.67 mm) by the quantity of 10 μl. The most powerful antifungal activity of caraway was observed against E. herbariorum as growth was completely inhibited by the quantity of 10 μl. The weakest inhibitory effect was observed against A. niger (inhibition zone 28 mm) by the quantity of 10 μl. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 31029]